Midwives as expert witnesses in the 18th-century Finnish courts of justice - Vainio-Korhonen K (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
In this article, I will explore how legalized Finnish midwives acted as expert witnesses in court hearings before 1809, how they worded the statements they gave in court, on what grounds they decided a woman was pregnant or had given birth, and what signs they considered as indicating a miscarriage or the birth of a full-term infant. Their work as expert witnesses relied on their midwifery training as well as their learned knowledge of the anatomy of the female body and the physiology of birth. Ultimately, their knowledge was supported by contemporary guidebooks on midwifery and forensic medicine. As expert witnesses, the trained and legalized midwives of the eighteenth century can be seen as having been legally literate women, who had a duty to provide oral or written evidence to the court and other instances who demanded it. Midwives were capable of using understandable medical and legal terminology in terms of the processing of the court case in their testimony. The forensic examinations carried out by legalized midwives and the expert witness statements they gave also demonstrate the professional skills and expertise of these women.. Their testimonies also show that they were familiar with the characteristics of infanticide referred to in the Swedish medical and forensic literature.